An approach for the definition of construction and maintenance strategies for flexible pavements - Sousa, Jorge B. (1998)
Design, Build, Finance and Operate contracts to develop a road network require a re-evaluation of the strategic decisions towards the design and maintenance strategies of flexible pavements. Probabilistic analysis, based on the variability of pavement material properties and layer thickness as well as on traffic variability is required and needed as a cost effective basis for the many possible design and maintenance strategies. The NOAH software was used to combine hundreds of possible design scenarios on a compressive basis for the decision making process towards a design criteria. The use of Rosenblueth transformations permitted the reduction of computational efforts and made possible the conclusion of this comprehensive design approach within the time frame of the tender. The bases for the data variability parameters were actual measurements made in the existing 83 km of freeway. Data from cores and from back-calculation analysis with the FWD in the determination of stiffness layer moduli was used. Permanent deformation (structural) and flexural fatigue failure criteria used was based on SHELL´s criteria. The roughness (IRI) induced cost, based on the World Bank model, was also used as a part of a life cycle cost analysis.